2023
DOI: 10.1186/s10020-023-00610-z
|View full text |Cite
|
Sign up to set email alerts
|

Organ and cell-specific biomarkers of Long-COVID identified with targeted proteomics and machine learning

Abstract: Background Survivors of acute COVID-19 often suffer prolonged, diffuse symptoms post-infection, referred to as “Long-COVID”. A lack of Long-COVID biomarkers and pathophysiological mechanisms limits effective diagnosis, treatment and disease surveillance. We performed targeted proteomics and machine learning analyses to identify novel blood biomarkers of Long-COVID. Methods A case–control study comparing the expression of 2925 unique blood proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 110 publications
1
16
0
Order By: Relevance
“…We recently reported that vascular transformation biomarkers were significantly elevated in plasma from Long-COVID outpatients (e.g., ANGPT1, MMP1, VEGF-A, etc. ), suggesting that angiogenesis may be a common mechanism in these patients with prolonged and diffuse symptoms [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that vascular transformation biomarkers were significantly elevated in plasma from Long-COVID outpatients (e.g., ANGPT1, MMP1, VEGF-A, etc. ), suggesting that angiogenesis may be a common mechanism in these patients with prolonged and diffuse symptoms [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…ANGPT1 is increased in the MIS-C cohort and is angiogenic with vascular protective effects [ 99 ]. As a primary regulator of angiogenesis, ANGPT1 is highly elevated in Long-COVID patients [ 27 , 30 , 100 ]. PPBP, also known as CXCL7, is elevated in the MIS-C cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Pathology is the core medical discipline to bring proteomics to patients via a new class of “postgenomic” protein-directed assays for early disease detection, risk prediction, choice of therapy and combination therapies, and surveillance. Combined with improvements in instrument design, orthogonal , and multiomic approaches, rapid progress in advanced computational capabilities including AI and machine learning , can now facilitate the development of personalized/precision medicine for the improvement of human health. ,, …”
Section: Pathology Pillarmentioning
confidence: 99%